Immunosuppressive effect of extracts from leaves of Fraxinus Mandshurica Rupr. Issue 3 (4th May 2017) - Chen, Yujuan; Xue, Gang; Liu, Feizhou; Gong, Xiuling
ABSTRACT: Plants provide a rich resource of medicinal material for research and development of new medicine. To discover new compounds as Immunosuppressant from plants, we evaluated the immunosuppressive effect of different fractions and particularly one compound (Calceolarioside A) that were extracted from the leaves of Fraxinus Mandshurica Rupr. The fractions and the compound were tested on the ability to reduce Immunoglobulin E (IgE) secretion by human U266 multiple myeloma cells (U266 cells) and to reduce interleukin-2 (IL-2) secretion by mouse spleen cells. Our results showed that both the butanol extract fraction and the compound of Calceolarioside A inhibited the IgE and IL-2 production in U266 cells and mouse spleen cells respectively, and no cytotoxicity was observed within the effective dose range. These results suggest that Calceolarioside A could potentially serve as an immunosuppressant.